THE IMPACT OF SERVANT LEADERSHIP ON ORGANIZATIONAL COMMITMENT: A FIELD STUDY AT THE TECHNICAL INSTITUTE\ AL-DOUR - Bassam Ali Khalid (Scholar Express Journals, 2025)
This research investigates the impact of servant leadership —as an independent variable— and its key dimensions (empowerment, altruism, love, and humility) on organizational commitment, which serves as the dependent variable with its own components. The study was conducted at the Technical Institute of AlDour. The core research question asked whether servant leadership influences organizational commitment. To explore this, a theoretical framework was developed to illustrate the anticipated relationships and effects between servant leadership and organizational commitment, forming the basis for several main and sub-hypotheses. A descriptive-analytical approach was adopted, with data collected through a structured questionnaire. The target sample included 121 employees (faculty, technicians, and administrators), from which 110 responses were obtained 11 of which were excluded due to invalidity. The data were analyzed using SPSS, and the reliability of the questionnaire was verified using Cronbach’s alpha coefficient. The results, based on the participants' high response levels, revealed a statistically significant and strongly positive correlation between servant leadership and organizational commitment at the institute. In light of these findings, the study concludes with a set of actionable recommendations aimed at fostering organizational commitment through the application of servant leadership principles.
Keywords: Servant Leadership; Organizational Commitment; Technical Institute Al-Dour